No Effect of Intravenous Actovegin® on Peak Aerobic Capacity - Lee, P.; Nokes, L.; Smith, P. M. (International Journal of Sports Medicine, 2012)
There is much speculation that Actovegin® is ergogenic, but no scientific work has been published in this field. 8 participants [mean(± SD) age, height and mass of 24 (7) years, 1.76 (0.07) m and 80.1 (9.1) kg, respectively] completed 3 exhaustive arm crank ergometry tests. Following Baseline testing 2 further tests were performed 2 h following the injection of either 40 ml of Actovegin® or a saline Placebo. Peak power (Wpeak), peak physiological responses, concentrations of blood glucose and lactate, exercise efficiency (%), VO2 gain (ml·W-1), and the respiratory compensation point (RCP) were determined. Repeated measures ANOVA tests were used to analyse data with significance accepted at p≤0.05. Values of mean (±90% CI) bias were calculated to further explore quantitative differences between trials. Strong trends for variations in Wpeak (p=0.054) and RCP (p=0.054) were evident; likely meaningful effects existed between the Baseline and both injection trials, but only a trivial effect was noted between Placebo and Actovegin® (bias: Wpeak 0.8±3.2 and RCP; 2.5±4.7 W). Concentrations of blood lactate and glucose changed across time, but did not differ between the 3 trials. Our data suggests the Actovegin® is not ergogenic and did not influence functional capacity in the context of the exhaustive, upper-body test employed.
Keywords: drug injection; ergogenic aid; doping; arm crank ergometry; haemodialysate